Biomechanical and Non-Biomechanical Strategies for Dance Injury Prevention: A Literature Review - Xiao, ChengYe; Wahid, Nurulakmal Abdul (Global Journal of Social Learning, 2025)
Dancers face a high risk of injury due to the biomechanical and artistic demands of training and performance. This study aims to review the efficacy of biomechanical and non-biomechanical interventions for injury prevention in dance. A literature search was conducted using Google Scholar with the keywords “injury prevention” + dance + RCT , limited to publications from the past five years (2021–2025). From the first 50 search results, and after removing duplicates and screening abstracts and full texts, 43 articles were included in the final analysis. Findings indicate that a wide range of interventions have been explored, with varying levels of evidence for their effectiveness. Biomechanical approaches such as neuromuscular training, strength and conditioning, and balance-focused programs were generally associated with positive outcomes in reducing injury risk and improving movement efficiency. However, their effectiveness often depended on the alignment of the program with dancers’ specific training contexts and developmental stages. Non-biomechanical interventions—including education, injury surveillance, workload management, and psychosocial support—were less frequently tested in randomized designs but offered promising complementary benefits, particularly in enhancing injury awareness, promoting safer training behaviors, and fostering a supportive performance environment. Mixed interventions that combined physical training with educational or participatory components showed the most consistent positive outcomes. These results highlight the importance of multidimensional strategies tailored to the unique needs of dance populations.